Aspects of Spinorial G-Structures - Bhoja, Niren (2024)
There is a remarkable isomorphism between a pair (metric, spinor), and a certain collection of differential forms on a manifold $M$. This isomorphism holds for numerous examples from four dimensions to eight dimensions.